2014
DOI: 10.1016/j.cub.2014.06.024
|View full text |Cite|
|
Sign up to set email alerts
|

Retromer Binding to FAM21 and the WASH Complex Is Perturbed by the Parkinson Disease-Linked VPS35(D620N) Mutation

Abstract: SummaryRetromer is a protein assembly that plays a central role in orchestrating export of transmembrane-spanning cargo proteins from endosomes into retrieval pathways destined for the Golgi apparatus and the plasma membrane [1]. Recently, a specific mutation in the retromer component VPS35, VPS35(D620N), has linked retromer dysfunction to familial autosomal dominant and sporadic Parkinson disease [2, 3]. However, the effect of this mutation on retromer function remains poorly characterized. Here we establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
189
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(215 citation statements)
references
References 27 publications
(39 reference statements)
25
189
1
Order By: Relevance
“…Mutations in VPS35, VPS26A and the retromer accessory protein DNAJC13 [43][44][45][46] have been associated with late-onset autosomal dominant Parkinson's disease (PD) [47][48][49][50]. Indeed, the PD-linked VPS35(p.D620N) mutation displays a reduced ability to associate with the actin polymerizing WASH (Wiskott-Aldrich syndrome protein and SCAR Homology) complex [51][52][53] which leads to altered endosome-to-Golgi transport and autophagosome formation [54,44,55,56]. Perturbed function of the WASH complex is also implicated in hereditary spastic paraplegia [57].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in VPS35, VPS26A and the retromer accessory protein DNAJC13 [43][44][45][46] have been associated with late-onset autosomal dominant Parkinson's disease (PD) [47][48][49][50]. Indeed, the PD-linked VPS35(p.D620N) mutation displays a reduced ability to associate with the actin polymerizing WASH (Wiskott-Aldrich syndrome protein and SCAR Homology) complex [51][52][53] which leads to altered endosome-to-Golgi transport and autophagosome formation [54,44,55,56]. Perturbed function of the WASH complex is also implicated in hereditary spastic paraplegia [57].…”
Section: Discussionmentioning
confidence: 99%
“…WASH is recruited to retromer-positive endosomal subdomains via the interaction of the extended C-terminal tail of FAM21 with the retromer subunit VPS35 (Harbour et al, 2012;Jia et al, 2012). Interestingly, a mutation in VPS35 (D620N) (Vilariño-Güell et al, 2011;Zimprich et al, 2011) that is associated with earlyonset Parkinson's disease has been shown to diminish the interaction of the SHRC with VPS35 and impair vesicular trafficking from the late endosome (Follett et al, 2013;McGough et al, 2014;Zavodszky et al, 2014). Studies in Drosophila have recently shown important roles for WASH in regulating integrin receptor trafficking and lysosome acidification (Nagel et al, 2017).…”
Section: Jmymentioning
confidence: 99%
“…Structurally, the retromer is comprised of two distinct subcomplexes: a cargo-recognition VPS26-VPS29-VPS35 heterotrimer and a membrane-targeting dimer of the sorting nexin (SNX1 and/or SNX2). Cell biological studies have shown that the PD-linked D620N VPS35 mutant associates poorly with the WASH (Wiskott-Aldrich syndrome protein and SCAR homolog) complex and impairs WASH recruitment to the endosomes (McGough et al 2014). Interestingly, autophagy is impaired in cells expressing the PD-mutant VPS35 or lacking WASH, which could be explained, at least in part, by the abnormal trafficking of ATG9A, a transmembrane protein that is required for autophagosome biogenesis (Zavodszky et al 2014).…”
Section: Membrane Trafficking Defect In Parkinson's Diseasementioning
confidence: 99%